PERSEPSI MAHASISWA DALAM PEMBELAJARAN BAHASA INGGRIS TERHADAP KARIR MAHASISWA VOKASI - Sriyanto, Widi; Dian Aprilyani Azir, Ince; Sitorus, Nurianti (Politeknik Negeri Bengkalis, 2023)
Abstract This study aims to explore the perceptions of vocational students towards learning English and its relationship with their views on career potential after graduation. Learning English at vocational colleges has an important role in preparing students to face an increasingly global world of work. However, several issues and challenges may arise in integrating learning English with the career goals of vocational students. This research method uses a qualitative approach with in-depth interviews and content analysis to collect data from different samples of vocational students. The information collected will reveal the views and expectations of students regarding learning English and how their perceptions relate to career opportunities after graduation. The results of this research are expected to provide valuable insights for vocational tertiary institutions and English teachers in developing a more relevant and effective curriculum. In addition, the research results can also help vocational students understand the benefits of learning English and how to prepare for career success in this global era. Keywords: Perception, student, learning English, career, vocation.